Enhancing Purchase Interest and Purchase Decisions: Discount and Brand Image for Skintific Products - Faizah Dwi Julianti; Hapzi Ali; Hadita Hadita; Matdio Siahaan; Ni Nyoman Sawitri (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
The increasingly competitive skincare industry is driving companies to implement marketing strategies capable of boosting consumer purchase intent and purchase decisions. This study aims to analyze the direct and indirect effects of discount and brand image on purchase decisions through purchase intent as an intervening variable for Skintific products. This study employs a quantitative approach using purposive sampling with 150 respondents. Data were collected through a questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that discount and brand image have a positive and significant direct effect on purchase interest and purchasing decisions, as well as an indirect effect on purchasing decisions through purchase interest as an intervening variable. Thus, purchase intention was found to mediate the effects of discount and brand image on the purchase decision for Skintific products.